Fever in a returning traveler: A case and literature review of melioidosis. (2021) - Arya, Akanksha; Shaikh, Hamadullah; Weber, Devin; Pettengill, Matthew; Moss, Sean
Abstract: Burkholderia pseudomallei is an aerobic, motile, non-spore-forming gram-negative bacillus found in tropical endemic environments that causes the disease melioidosis. Melioidosis displays a diversity of clinical presentations ranging from septic shock to chronic latent infection, often with characteristic abscesses in multiple organs. Melioidosis is an opportunistic infection, with risk factors, including diabetes, alcohol use, chronic lung disease, and chronic renal disease, and these risk factors increase the severity of disease (Wiersinga et al., 2006) [1] . In this case report, we illustrate a case of a 32 year old man with several risk factors and recent travel to an endemic region presenting with melioidosis. Our case demonstrates the challenges in obtaining a diagnosis in a non-endemic location, highlights a complex presentation of this disease, and describes the multifaceted clinical management required to care for this patient. As global travel increases, there is an increased need for clinician awareness of this disease in non-endemic regions.